Analysis of Land Availability and Land use Directions in the East Development Area of Bogor District - Dewantoro, Hanang; Trilusianthy Hidayat, Janthy; Sri Mulyawati, Lilis (Journal of Social Science, 2024)
This paper investigates the suitability and availability of land for development in the Eastern Development Region (WP Timur) of Bogor Regency, West Java. As part of the Jakarta, Bogor, Depok, Tangerang, Bekasi, Puncak, Cianjur (Jabodetabekpunjur) National Strategic Area, WP Timur plays a crucial role in urban development, environmental conservation, and agricultural expansion. This study utilizes Geographic Information System (GIS) tools and Analytic Hierarchy Process (AHP) combined with Strengths, Weaknesses, Opportunities, and Threats (SWOT) analysis to assess land use suitability and resolve land availability issues. The research identifies that a significant portion of WP Timur's current land use comprises rainfed paddy fields, irrigated rice fields, and productive mixed gardens. These are essential for local agriculture but must align with the Regional Spatial Plan (RTRW) of Bogor Regency to support sustainable urbanization and industrial development. Analysis reveals challenges related to land conflicts and legal disputes, highlighting the need for clear land tenure and effective management strategies. By evaluating existing land use against the RTRW guidelines, the study identifies suitable and unsuitable areas for various land uses, emphasizing the importance of integrated spatial planning for balanced development. The findings provide valuable insights for policymakers and urban planners to optimize land utilization, enhance regional competitiveness, attract investments, and improve local community welfare in WP Timur. Keywords: land suitability, land availability, GIS, AHP, SWOT analysis, regional spatial planning.